2018
DOI: 10.1257/jep.32.3.3
|View full text |Cite
|
Sign up to set email alerts
|

What Happened: Financial Factors in the Great Recession

Abstract: At the onset of the recent global financial crisis, the workhorse macroeconomic models assumed frictionless financial markets. These frameworks were thus not able to anticipate the crisis, nor to analyze how the disruption of credit markets changed what initially appeared like a mild downturn into the Great Recession. Since that time, an explosion of both theoretical and empirical research has investigated how the financial crisis emerged and how it was transmitted to the real sector. The goal of this paper is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(36 citation statements)
references
References 44 publications
1
31
0
4
Order By: Relevance
“…In September 2008, Lehman Brothers became exposed to excess mortgage-related risks. As a result, the Federal Reserve was unable to act as a "lender of last resort," forcing Lehman Brothers to default because it could not offer sufficient collateral (Gertler & Gilchrist, 2018).…”
Section: The Great Economic Recessionmentioning
confidence: 99%
“…In September 2008, Lehman Brothers became exposed to excess mortgage-related risks. As a result, the Federal Reserve was unable to act as a "lender of last resort," forcing Lehman Brothers to default because it could not offer sufficient collateral (Gertler & Gilchrist, 2018).…”
Section: The Great Economic Recessionmentioning
confidence: 99%
“…This does suggest that more innovative younger firms are more willing to bear the external finance premium. This holds even during the crisis, when the external finance premium is elevated (Mark Gertler & Gilchrist, 2018). No corresponding relationships are found for older firms.…”
Section: What Are the Determinants Of Application For External Finance?mentioning
confidence: 84%
“…More recently, financial economists have shown that the loss in housing wealth (Mian and Sufi, 2010), a decrease in consumer credit (Mian, Rao, & Sufi, 2013), highly-levered households (Mian & Sufi, 2018) and panics from the collapse of Lehman Brother (Mian & Sufi 2015) led to a consumption-driven recession, reducing global demand. Some economists hold both these factors responsible (Gertler & Gilchrist, 2018).…”
Section: A Tale Of Two Effects Of the Gfc: Financing Smes And Innovative Financementioning
confidence: 99%
See 2 more Smart Citations